Making space for a case: an inquiry on the collaborative initiatives of selected public libraries in Metro Manila as points of access to justice - Castillo, Jan Francis O.
Access to Justice is a vital concept extending beyond traditional legal institutions, encompassing various organizations that help individuals navigate legal complexities and access essential resources. Public libraries, as accessible community spaces, offer unique opportunities for collaboration on justice-related initiatives. This study investigates the collaborative efforts of public libraries in Metro Manila and their impact on Access to Justice. It examines library staff perceptions to provide recommendations for enhancing the role of libraries in promoting equitable Access to Justice within their communities.